Replication of Marek's disease vaccines in turkey embryos and their effect on TLR-3 and IFN-γ transcripts. Issue 3 (4th May 2021) - Gimeno, I. M.; Shaw, W. N.; Turner, A.; Bremen, J.; Cortes, A. L.; Faiz, N. M.; Gonder, E.; Robbins, K.
ABSTRACT: Understanding the pathogenesis of herpesvirus of turkeys (HVT) in its natural host is necessary before recombinant HVT (rHVT) can be used efficiently in turkey flocks. The objectives of this study were to evaluate when commercial turkey flocks get infected with wild type HVT, to study replication of HVT (conventional and recombinant rHVT-Newcastle disease, rHVT-ND) and other Marek's disease (MD) vaccines (SB-1 and CVI988) in turkey embryonic tissues, and to evaluate the expression of TLR-3 and IFN-γ in the lung and spleen of one-day-old turkeys after in ovo vaccination with MD vaccines. Our results demonstrated that commercial turkeys got exposed to wild type HVT within the first days of life; therefore, there is a potential of interaction between wild type HVT and rHVT when administered at day of age. On the other hand, all evaluated vaccines (especially HVT and rHVT-ND) replicated very well in turkey embryonic tissues. In ovo vaccination with HVT and CVI988 increased transcription of TLR-3 in the spleen of one-day-old turkeys. However, no effect on the transcription of TLR-3 or IFN-γ in the lungs and IFN-γ in the spleen in newly hatched turkeys was detected in the present study. Because of the limitations of evaluated genes, timepoints, and studied tissues, future studies are warranted to better understand the effect of MD vaccines on the turkey embryo immune responses. RESEARCH HIGHLIGHTS Commercial turkey flocks get infected with wild type HVT within the first days of life. HVT and rHVT replicates readily in turkey embryonic tissues. SB-1 and CVI988 also replicate in turkey embryonic tissues, but at lower rates than HVT and rHVT. HVT and CVI988 increase transcription of TLR-3 in the spleen.